Bacterial and Fungal Coinfections in COVID-19 Inpatients at a Tertiary Hospital in Surabaya, Indonesia, from November 2020 to February 2022 - Naura Ghina Shabira; Agung Dwi Wahyu Widodo; Musofa Rusli (Current Internal Medicine Research and Practice Surabaya Journal)
Introduction: After the first discovery of coronavirus disease 2019 (COVID-19) in 2020, the rapid increase of cases beyond China prompted the declaration of a pandemic. Elevated rates of bacterial-fungal coinfection were observed in hospitalized COVID-19 patients. This study aimed to determine the profiles of bacterial and fungal coinfections in COVID-19 patients diagnosed between November 2020 and February 2022 at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.